Synthesis of melt-quenched Bi1.7V0.3Sr2Ca2Cu3O10+y superconducting glass-ceramics - Yakinci, ME; Aksoy, I; Ceylan, M (Springer, 1996)
A glass in the BSCCO system with Bi1.7V0.3Sr2Ca2Cu3O10+y nominal composition was prepared by the melt-quenching (glass) method. The suitability of the glass ceramic method has been assessed in terms of physical and electrical properties. Using an analysis developed for non-isothermal crystallization studies, information on some aspects of crystallization has been obtained. The result obtained indicated that substitution of vanadium for bismuth increased the activation energy compared to the unsubstituted BSCCO system but did not enhance the superconducting phase formation. The activation energy for crystallization of glass has been found, E(a)=355 kJ mol(-1). The crystal structure was found to differ from that in the unsubstituted BSCCO system. Most importantly, the HT, phase was formed by reaction between the constituent phases at lower temperatures and not directly from the glass material. The best electrical properties were obtained at T-0=75 K and J(c)=12 x 10(3) A cm(-2) at 4.2 K.
Keywords: Cu-O System; Crystallization